Determinants of Health Literacy and Healthy Lifestyle against Metabolic Syndrome among Major Ethnic Groups of Sarawak, Malaysia : A Multi-Group Path Analysis - Froze, S.; M. T., Arif; Rosalia, Binti Saimon (Bentham Science Publishers, 2019)
Introduction: Non-communicable diseases like metabolic syndrome can be prevented and controlled by practicing healthy lifestyle. Although health literacy is a critical factor in lifestyle modification to prevent non-communicable diseases and its complications, its role on metabolic syndrome prevention is still understudied. Objective: The main aim of this study was to identify the determinants of health literacy and healthy lifestyle practice against metabolic syndrome among multi-ethnic group of Sarawak based on health literacy skills framework. Methods: Using a stratified multistage sampling, a total of 1006 respondents were recruited to represent the major ethnic groups in Sarawak, Malaysia. Moderator variables, mediator variables and outcome variable (healthy lifestyle practice) were tested using path analysis to examine multiple and interrelated dependence relationships. Multi-group analysis was performed to compare structural models between major ethnic groups in Sarawak, namely Malay/Melanau, Native groups and Chinese. Results: Female respondents and those with higher education status were more likely to have better healthy lifestyle practice. Greater level of health literacy was positively significant with both disease knowledge and healthy lifestyle practice. Participants with good understanding of disease knowledge can directly influence healthy lifestyle. Simultaneously, health literacy and metabolic syndrome knowledge can mediate the relationship between sociodemographic variables, service accessibility, medical and family history with practice of healthy lifestyle. Multi-group path analysis indicated differences in causal pathway leading to healthy lifestyle practice among the ethnic groups.